2014
DOI: 10.1104/pp.114.246207
|View full text |Cite
|
Sign up to set email alerts
|

Increased Ratio of Electron Transport to Net Assimilation Rate Supports Elevated Isoprenoid Emission Rate in Eucalypts under Drought    

Abstract: Plants undergoing heat and low-CO 2 stresses emit large amounts of volatile isoprenoids compared with those in stress-free conditions. One hypothesis posits that the balance between reducing power availability and its use in carbon assimilation determines constitutive isoprenoid emission rates in plants and potentially even their maximum emission capacity under brief periods of stress. To test this, we used abiotic stresses to manipulate the availability of reducing power. Specifically, we examined the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 70 publications
(77 reference statements)
2
37
0
Order By: Relevance
“…Additional studies revealed possible connections between volatile isoprenoid emissions and increased photorespiration during high leaf temperatures and drought stress (Dani et al, 2014). Consistent with these potentially important functional roles for pioneer species, a leaf and branch survey at four neo-tropical sites (Harley et al, 2004) suggested that Vismia guianensis is an Is producer with a single leaf emission value of 48 µg C g −1 h −1 reported (or 11 nmol m −2 s −1 assuming a specific leaf area of 20 m 2 kg −1 ) (Dias-Filho, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies revealed possible connections between volatile isoprenoid emissions and increased photorespiration during high leaf temperatures and drought stress (Dani et al, 2014). Consistent with these potentially important functional roles for pioneer species, a leaf and branch survey at four neo-tropical sites (Harley et al, 2004) suggested that Vismia guianensis is an Is producer with a single leaf emission value of 48 µg C g −1 h −1 reported (or 11 nmol m −2 s −1 assuming a specific leaf area of 20 m 2 kg −1 ) (Dias-Filho, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The emission rates observed in all of our experiments involving eucalypts, including both multiple species and the pairwise comparison cited above, 16 were low (0 to 10 nmol/m 2 /s) compared with those from more widely studied poplars and oaks (20 to 100 nmol/m 2 /s). 6 Many native Australian plants have abundant Rubisco and eucalypts in particular are notable for their extremely high photosynthetic capacities among trees, operating as they generally do in high-light environments.…”
mentioning
confidence: 59%
“…Improving global emission algorithms requires a broad consensus of species' responses to drought, which so far has proven a challenge. In this addendum to Keywords: drought, electron transport rate, isoprene emission, MEP pathway, photorespiration the paper by Dani et al, 16 we highlight issues that are yet to be addressed.…”
mentioning
confidence: 97%
See 2 more Smart Citations